0.5-V Mixed-Mode Universal Active Filter Using Multiple-Input OTAs - Phatsornsiri, Punnavich; Kumngern, Montree; Nonthaputha, Thanat; Asa, Ekachai; Singsathien, Jateslid; Moungnoul, Phichet (My University, 2024)
This study introduces new 0.5 V, ultra-low power mixed-mode universal analog filter applying multiple-input operational transconductance amplifiers (MI-OTAs). The filter configuration based on MI-OTAs and two grounded capacitors to actualize a mixed-mode universal filter that can produce four modes second-order filters, that is low-pass, high-pass, band-pass, band-stop and all-pass filters, namely voltage-mode, current-mode, transimpedance mode, transconductance-mode, by appropriate selecting input signals. The filter's natural frequency can be electronically controlled. The mixed-mode filter was analyzed using CMOS 0.18μm process simulation from TSMC, operating with a 0.5 V power supply.
Keywords: Active filter; bulk-driven MOS transistor; mixed-mode filter; operational transconductance amplifier